2018
DOI: 10.1136/bcr-2017-221714
|View full text |Cite
|
Sign up to set email alerts
|

A case of platypnoea orthodeoxia following Laproscopic Cholecystectomy

Abstract: Platypnoea Orthodeoxia syndrome is defined by dyspnoea and hypoxaemia exacerbated by orthostatic positioning and alleviated in recumbency. This condition has been reported in association with pulmonary, hepatic and cardiac disease. We describe a case herein of a 79 year old female who developed severe hypoxaemia and dyspnoea post laparoscopic cholecystectomy. A difference in arterial blood gas oxygen tension was demonstrated in the supine and erect positions on arterial blood gas analysis. A Patent Foramen Ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…PFO is thought to be present in 25% of the population; however, clinically significant right-to-left shunting is rare and requires raised right atrial pressure 3. Riddles et al 4 reported a case of POS following laparoscopic cholecystectomy. Other case studies also indicate that surgery is a common precipitant for the development of POS 5–8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PFO is thought to be present in 25% of the population; however, clinically significant right-to-left shunting is rare and requires raised right atrial pressure 3. Riddles et al 4 reported a case of POS following laparoscopic cholecystectomy. Other case studies also indicate that surgery is a common precipitant for the development of POS 5–8.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for mechanisms that maintain postoperative right-to-left shunting remain speculative. Riddles et al 4 suggested that ‘a common postoperative complication of atelectasis may increase pulmonary vascular resistance and cause a V/Q mismatch’. While the patient in the present case study had left lower lobe atelectasis, it is unlikely to be the only explanation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been multiple case reports of hypoxaemia due to acquired right-to-left shunts in patients with a PFO following thoracic or laparoscopic abdominal surgery. 43,44 While not completely understood, patients who develop unexplained hypoxaemia after the operation should be considered for a transthoracic echocardiogram and bubble study to assess for PFOs.…”
Section: Postoperative Unexplained Hypoxaemiamentioning
confidence: 99%